Using input output analysis framework to explain economic diversification and structural transformation in Bangladesh. - Mercer Blackman, Valerie (Metro Manila, Philippines Asian Development Bank, 2017)
Using input output tables, this paper develops a framework for considering economic diversification across manufacturing and services and global value chain insertion as an integral part of economic development. New indicators are developed to characterize the structural transformation that occurs across production sectors and the links required to ensure broad based development. Bangladeshs export-led growth in the last two decades, which has been concentrated in ready-made garments, is also examined.
Keywords: Diversification industries -- Bangladesh; Electronic books